2006
DOI: 10.1093/occmed/kql054
|View full text |Cite
|
Sign up to set email alerts
|

Incentives for voluntary HIV testing in NHS staff

Abstract: Since the NHS is recruiting staff from areas of high HIV prevalence, VCT should be encouraged. NHS staff require information on how to access testing as well as the benefits of early detection of blood-borne viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 2 publications
0
12
1
1
Order By: Relevance
“…However, according to the 2005 Ethiopia Demographic Health Survey, 4% of women and 6% of men had ever been tested for HIV [33]. Studies conducted in Zambia, Zimbabwe and the UK reported that acceptance of HIV testing was lower among women than men [20,34,35]. The Zimbabwean study specifically reported that women were allegedly more worried about their HIV status and more fearful of HIV testing than men [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, according to the 2005 Ethiopia Demographic Health Survey, 4% of women and 6% of men had ever been tested for HIV [33]. Studies conducted in Zambia, Zimbabwe and the UK reported that acceptance of HIV testing was lower among women than men [20,34,35]. The Zimbabwean study specifically reported that women were allegedly more worried about their HIV status and more fearful of HIV testing than men [34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in the review (including both public and HCP attitudes to testing) were peer reviewed papers (n= 40) [16,[24][25][26][27][28]30,32,33,35,[38][39][40][41]43,[45][46][47][48][49][50][52][53][54][55][56][57]59,61,62,65,69,71,72,75,79,80,84] abstracts from BHIVA conference proceedings (n=20) [29,31,36,37,42,51,58,60] and published reports (n=4) [34,44,85]. UK locations of included studies were as follows; Scotland (n=9) [34,…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The majority of the studies were conducted in areas of high HIV prevalence (> 2/1000 adult population) such as London, Brighton and Glasgow. Studies used a variety of different data collection methods which included: questionnaires (n= 29) [31,33,35,[38][39][40][41]47,48,[51][52][53]55,58,59,60,62,65,66,67,70,71,73,74,75,76,78] focus groups (n=5) [32,51,54 69,84] interviews (n=4) [29,30,50,56], surveys (n=13) [16,24-28, 44,64,68,72,77,80,85], questionnaires and surveys (n=1) [43], questionnaires and focus groups (n=1) [61], interviews and focus groups (n=3) [45,46,49], interviews and questionnaires (n=2) (study included in Table 1 (public attitudes) and also Table 2 (HCP attitudes) [34], survey and questionnaire (n=1) [43], survey and interviews (n=1) [63], audit and questionnaires (n=1) [79], and reviews of case notes/admission notes (n= 3) ...…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations